Effects of Lavender and Linalool on Neurotransmission and Contraction of Smooth Muscle - Poyton, Curtis; Manchadi, Mary-Louise; Cheesman, Matthew; Lavidis, Nickolas (Pharmacognosy Communications)
Introduction:Lavender (Lavandula angustifolia) is commonly used in household products, perfumes, aromatherapy and complementary medicines. This study assesses the effects of lavender and its component linalool on neurotransmission and contraction of smooth muscle. Methods: The concentration-dependent effects of lavender (0.001% to 0.05%) and linalool (0.001% to 0.05%) on electrically evoked nerve terminal impulse (NTI) and excitatory junction current (EJC) amplitudes were assessed, while the effects of lavender (0.03%) and linalool (0.03%) on 5-hydroxytryptamine, acetylcholine, histamine, noradrenaline and oxytocin evoked responses were examined. Reversibility of lavender (0.03%) and linalool (0.03%) effects on electrically evoked NTI and EJC amplitudes, as well as on acetylcholine evoked contractile responses, were also analysed. Results: Lavender and linalool caused concentration-dependent decreases of electrically evoked NTI and EJC amplitudes, and attenuated the contractile responses towards 5-hydroxytryptamine, acetylcholine, histamine, noradrenaline and oxytocin. Repeated washing of tissues treated with lavender following pre-treatment with acetylcholine reversed the inhibitory effects of lavender, whereas linalool’s effects were not readily reversible. Conclusion: Lavender and linalool may cause inhibition of smooth muscle presynaptic action potential propagation and postsynaptic G-protein coupled receptor evoked responses.
Keywords: Excitatory junction current; G-protein coupled receptor; Lavandula angustifolia; Linalool; Nerve terminal impulse; Smooth muscle contraction; Synapses